Exploring efficiency growth of advanced technology-generating sectors in the European Union: a stochastic frontier analysis - Dzemydaitė, Giedrė; Naruševičius, Laurynas (Journal of Business Economics and Management, 2023)
This study investigates the efficiency growth of advanced technology-generating sectors within the European Union (EU). Using a stochastic frontier analysis of annual sector-level panel data from 2000 to 2019, we examine sectoral (NACE two-digit level) and territorial implications. Our findings indicate that technological change was more intense in advanced technology-generating sectors than in other economic sectors, primarily driven by fixed capital investments. However, the impact of in-house research and development varied. Economic sectors such as pharmaceuticals and motor vehicles struggled to improve their production efficiency due to high competition and market specificity. A comparative analysis of EU economies showed a lower level of production efficiency in catching-up economies. Nevertheless, these economies contributed to the shift of the production possibility frontier in certain sectors on the EU level. Therefore, this study contributes to the ongoing scientific discussion on technological innovations in diverse territories, suggesting that less-developed economies could generate technological advancements in specific areas. We also discuss the implications for innovation and industrial policy actions. First published online 09 January 2024